Tantangan Etika Jurnalisme Online: Studi Kasus Pemberitaan Jawapos.com dalam Konteks Regulasi UU ITE - Muh. Mahsya Nawaffani; Faruq Alhasbi; Nafi’ Hanifah; Ibni Nur Salamah Haryanto (Pawarta: Journal of Communication and Da'wah, 2025)
Rapid advances in information technology have transformed news consumption toward online platforms, incentivizing speed and traffic-driven content that often yields sensational headlines (clickbait) and weak verification practices; two JawaPos.com reports serve as case points illustrating how media framing can carry ethical and legal ramifications in the digital news ecosystem. This study aims to examine how framing in two articles on JawaPos.com shapes public narratives and to assess the implications for journalistic ethics and Indonesia’s Electronic Information and Transactions Law (UU ITE). A qualitative case study approach was employed, with textual analysis of the selected news items as the primary unit. Data were collected from archived news content, legal documents (UU ITE, Press Council’s Cyber Media Guidelines), and academic literature. Robert N. Entman’s framing model (define problems, diagnose causes, make moral judgment, suggest remedies) guided the analysis, accompanied by source triangulation to ensure validity. Results indicate both reports rely on emotionally charged diction and social-media–sourced opinions without adequate verification; the “suggest remedies” element is largely absent, undermining balance and fact-checking. Such framing practices pose legal risks, potentially implicating Clauses 27A, 28(1), and 45A of the UU ITE, as the publication of unverified identities and allegations may harm personal reputations and propagate misleading information. Online newsrooms must strengthen editorial controls and layered verification procedures, aligning newsroom practices with cyber media guidelines and UU ITE, to preserve journalistic integrity and mitigate legal exposure. Perkembangan teknologi informasi menggeser konsumsi berita ke ranah daring dan mendorong praktik pemberitaan yang mengedepankan kecepatan serta trafik, yang sering kali berujung pada headline sensasional (clickbait) dan pengabaian verifikasi. Dua kasus pemberitaan di JawaPos.com menjadi ilustrasi terkait dampak framing dan potensi implikasi hukum dalam konteks media daring. Penelitian ini bertujuan mengkaji bagaimana framing pemberitaan pada dua artikel JawaPos.com membentuk narasi publik dan menilai implikasinya terhadap etika jurnalistik serta ketentuan Undang-Undang Informasi dan Transaksi Elektronik (UU ITE). Pendekatan kualitatif studi kasus digunakan dengan analisis teks sebagai unit analisis, data dikumpulkan melalui dokumentasi arsip berita, peraturan hukum (UU ITE, Pedoman Media Siber), dan literatur relevan. Analisis menggunakan model framing Robert N. Entman (define problems, diagnose causes, make moral judgment, suggest remedies) serta triangulasi sumber untuk menjaga validitas. Temuan menunjukkan bahwa kedua pemberitaan cenderung mengutamakan diksi dramatis dan sumber opini netizen tanpa verifikasi memadai, tahap “suggest remedies” minim atau absen, sehingga keberimbangan dan verifikasi terabaikan. Framing tersebut berpotensi menimbulkan konsekuensi hukum, khususnya terkait Pasal 27A, 28 ayat (1), dan 45A UU ITE, karena pemuatan identitas dan tuduhan yang belum terkonfirmasi dapat merugikan reputasi individu dan memicu penyebaran informasi menyesatkan. Media daring perlu memperkuat mekanisme editorial dan verifikasi, serta mengharmonisasikan praktik redaksional dengan Pedoman Media Siber sesuai ketentuan UU ITE untuk menjaga integritas jurnalistik dan mengurangi risiko hukum.